PEMBERDAYAAN BUMDES DAN PELATIHAN KETRAMPILAN USAHA DIDESA SIDAKARYA DENPASAR BALI - Suryathi, Wayan; Suamba, IB. Putu; Adiningrat, Gede Pradiva (Dharma: Jurnal Pengabdian Masyarakat, 2020)
BUMDes of Sidakarya Village has a srtrategic role to help public society, however it enquare an empowerment because it the effort of management new years old, as well the community need intensif of training. The aim of community dedication are getting empowerment of BUMDes and give the effort skill training for people in Sidakarya Village. The acitivity of community dedication areTraditional cooking training, Business Ethic and digital communication. Partner targeting of this program are BUMDes, Karang Taruna and PKK of Sidakarya Vallage. The methode of this activity are training, focus group discussion, deept interview and questionare. The result and external target from the dedication are the empowerment of BUMDes has been reached and the skill of effort training has been action. And obtained the value evaluation s very good